Emulation of Electromagnetic Plane Waves for 3D Antenna Pattern Estimation - Vintimilla, Renato Zea; Lorenz, Mario; Landmann, Markus; Galdo, Giovanni Del (IEEE Vehicular Technology Conference, 2022)
With the fast development of wireless devices, over-the-air (OTA) testing is becoming the preferred method among developers and manufacturers of wireless equipment. The ability to recreate a scenario under controllable and repeatable conditions keeps the method under constant development, providing new features that increase the realism during the tests. A recent proof of that is the integration of 3D wave field synthesis (3DWFS) to OTA testing, which becomes a significant step to accurately emulate wireless scenarios within a controlled environment.In this context, this contribution improves the OTA system calibration for 3DWFS; efficiently increasing the emulation quality of electromagnetic plane waves impinging from any angular position within an anechoic chamber. In fact, this enhancement implicitly delivers a new method for accurate estimation of the antenna radiation pattern in 3D. This is not only a highly demanded application among antenna manufacturers but in this case also proves the validity of the results and consolidates the integration of 3DWFS to OTA testing.
CRIS-Team Scopus Importer:2025-11-10
Keywords: 3d; antenna; electromagnetics; emulation; measurements; ota; pattern; wave field synthesis